Flexible Electricity Dispatch of an Integrated Solar Combined Cycle through Thermal Energy Storage and Hydrogen Production - Miguel Ángel Reyes-Belmonte; Alejandra Ambrona-Bermúdez; Daniel Calvo-Blázquez (Thermo, 2021)
In this work, the flexible operation of an Integrated Solar Combined Cycle (ISCC) power plant has been optimized considering two different energy storage approaches. The objective of this proposal is to meet variable users’ grid demand for an extended period at the lowest cost of electricity. Medium temperature thermal energy storage (TES) and hydrogen generation configurations have been analyzed from a techno-economic point of view. Results found from annual solar plant performance indicate that molten salts storage solution is preferable based on the lower levelized cost of electricity (0.122 USD/kWh compared to 0.158 USD/kWh from the hydrogen generation case) due to the lower conversion efficiencies of hydrogen plant components. However, the hydrogen plant configuration exceeded, in terms of plant availability and grid demand coverage, as fewer design constraints resulted in a total demand coverage of 2155 h per year. It was also found that grid demand curves from industrial countries limit the deployment of medium-temperature TES systems coupled to ISCC power plants, since their typical demand curves are characterized by lower power demand around solar noon when solar radiation is higher. In such scenarios, the Brayton turbine design is constrained by noon grid demand, which limits the solar field and receiver thermal power design.